Dietary Patterns in Relation to Low Bone Mineral Density and Fracture Risk: A Systematic Review and Meta-Analysis - Fabiani, Roberto; Naldini, Giulia; Chiavarini, Manuela (Advances in nutrition (Bethesda, Md.), 2019)
Low bone mineral density (BMD) and osteoporosis-related fractures constitute a considerable public health burden. Several studies have demonstrated the association between diet and bone health. We performed a systematic review to provide an estimate of the association between different dietary patterns defined through the use of a posteriori methods and fracture or low BMD risk. A literature search on PubMed, Web of Science, and Scopus databases, up to March 2018, was performed to identify all eligible case-control, prospective, or cross-sectional studies involving subjects of both sexes and any age. Random-effects models were used. Heterogeneity and publication bias were evaluated. Stratified analyses were conducted on study characteristics. The meta-analysis includes 20 studies and identifies 3 prevalent dietary patterns: “Healthy,” “Milk/dairy,” and “Meat/Western.” From the 10 studies on fracture, adherence to the “Healthy” pattern reduced the risk, particularly in older people (OR: 0.79; 95% CI: 0.66, 0.95; P= 0.011) and in Eastern countries (OR: 0.64; 95% CI: 0.43, 0.97; P= 0.037), whereas the risk increased with the “Meat/Western” pattern, especially for older people (OR: 1.11; 95% CI: 1.04, 1.18, P= 0.001), in those with hip fractures (OR: 1.15; 95% CI: 1.05, 1.25; P= 0.002), and in Western countries (OR: 1.10; 95% CI: 1.07, 1.14; P< 0.0001). Analyses on low BMD showed a reduced risk in the “Healthy” pattern, particularly for younger people (OR: 0.62; 95% CI: 0.44, 0.89; P= 0.009). The “Meat/Western” pattern increased low BMD risk, especially in older people (OR: 1.31; 95% CI: 1.05, 1.64; P= 0.015). The “Milk/dairy” pattern resulted in the strongest reduction in low BMD risk; when stratifying, this effect remained significant (e.g., older women—OR: 0.57; 95% CI: 0.46, 0.70; P< 0.0001). Nutrition is an important modifiable factor affecting bone health. The “Healthy” and “Milk/dairy” patterns are associated with a reduced risk of low BMD and fracture. In contrast, the “Western” pattern is inversely associated.